Cognitive remediation therapy for patients with bipolar disorder: A randomised proof‐of‐concept trial. (17th July 2020) - Strawbridge, Rebecca; Tsapekos, Dimosthenis; Hodsoll, John; Mantingh, Tim; Yalin, Nefize; McCrone, Paul; Boadu, Janet; Macritchie, Karine; Cella, Matteo; Reeder, Clare; Fish, Jessica; Wykes, Til; et al.
Abstract: Objectives: Cognitive remediation therapy (CRT) may benefit people with bipolar disorder type I and II for whom cognitive impairment is a major contributor to disability. Extensive research has demonstrated CRT to improve cognition and psychosocial functioning in people with different diagnoses, but randomised trials of evidenced therapy programmes are lacking for bipolar disorders. The Cognitive Remediation in Bipolar (CRiB) study aimed to determine whether an established CRT programme is feasible and acceptable for people with bipolar disorders. Methods: This proof‐of‐concept, single‐blind randomised trial recruited participants aged 18‐65 with bipolar disorder, not currently experiencing an episode. They were 1:1 block randomised to treatment‐as‐usual (TAU) with or without individual CRT for 12 weeks. The partly computerised CRT programme ("CIRCuiTS") was therapist‐led and is evidence‐based from trials in those with psychotic illnesses. Data were collected and analysed by investigators blinded to group allocation. The main outcomes (week 13 and 25) examined participant retention, intervention feasibility and putative effects of CRT on cognitive and psychosocial functioning via intention‐to‐treat analyses. Trial registration: ISRCTN ID32290525. Results: Sixty participants were recruited (02/2016‐06/2018) and randomised to CRT (n = 29) or TAU (n = 31). Trial withdrawals were equivalent (CRT n = 2/29; TAU n = 5/31). CRT satisfaction indicated high acceptability. Intention‐to‐treat analyses (N = 60) demonstrated greater improvements for CRT‐ than TAU‐randomised participants: at both week 13 and 25, CIRCuiTS participants showed larger improvements in the following domains (week 25 effect sizes reported here): IQ (SES = 0.71, 95% CI [0.29, 1.13]), working memory (SES = 0.70, 95% CI [0.31, 1.10]), executive function (SES = 0.93, 95% CI [0.33, 1.54]), psychosocial functioning (SES = 0.49, 95% CI [0.18, 0.80]) and goal attainment (SES = 2.02, 95% CI [0.89, 3.14]). No serious adverse events were reported. Conclusions: CRT is feasible for individuals with bipolar disorders and may enhance cognition and functioning. The reported effect sizes from this proof‐of‐concept trial encourage further investigation in a definitive trial.